Predictive Effects of Personality Traits on Job Stress among Secretaries in Olabisi Onabanjo University - Dosunmu, Margaret Moronke (NIU Journal of Humanities, 2018)
The study examined the predictive effect of Personality traits (Extraversion, agreeableness, conscientiousness, Neuroticism and openness to experience) on Job Stress of Secretaries in Olabisi Onabanjo University, Ogun State.  A descriptive survey research design was adopted for this study. The sample for this study comprised One hundred (100) Secretaries and Assisstant secretaries in State-owned universities of Ogun state. The data was collected using Job Stress Scale (r = 0.96) and Big Five Personality Scale (r = 0.80). Pearson Product Moment Correlation (PPMC) and Multiple Regression Analysis was used to analysed the three research questions raised at 0.05 level of significance. The result revealed that there are positive relationship between Extraversion and job stress of Secretaries, Agreeableness and job stress of secretaries, Conscientiousness and job stress of secretaries and Neuroticism and job stress of secretaries. Also there was a composite effect of Personality traits (Extraversion, agreeableness, conscientiousness, neuroticism and openness to experience) on job stress of secretaries. And Agreeableness was the most potent out of the predictor variables, followed by Conscientiousness. It was recommended among others that the management should have closer look at these factors as an initiative action to prevent high turnover in the organisation. Administrators should then design programs and trainings to help secretaries increase their level of satisfaction with personal learning and growth opportunities at work, job security, and compensation. Keywords: Predictive, Personality, Traits, Stress and Secretaries